2020
DOI: 10.1111/cas.14423
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐93 targets WASF3 and functions as a metastasis suppressor in breast cancer

Abstract: Cancer cells with cancer stem cell (CSC) properties initiate both primary tumor formation and metastases at distant sites. Acquisition of CSC properties is highly associated with epigenetic alterations, including those mediated by microRNAs (miRNAs). We have previously established the breast cancer patient‐derived tumor xenograft (PDX) mouse model in which CSC marker CD44+ cancer cells formed spontaneous microscopic metastases in the liver. In this PDX mouse, we found that the expression levels of 3 miRNAs (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
3
24
0
Order By: Relevance
“…In addition, KEGG analysis showed that the endocytic pathway is altered in cancer cells, and these alterations contribute to increased receptor recycling, thereby enhancing invasiveness 29 . MicroRNAs play their roles by suppressing the expression of target genes 30,31 . The biological interactions between miRNAs and their target genes are very complex 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KEGG analysis showed that the endocytic pathway is altered in cancer cells, and these alterations contribute to increased receptor recycling, thereby enhancing invasiveness 29 . MicroRNAs play their roles by suppressing the expression of target genes 30,31 . The biological interactions between miRNAs and their target genes are very complex 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Equal numbers of MDA‐MB‐231‐ZsGreen cells overexpressing S100A10 shRNA (shS100A10‐1 ZsGreen) and MDA‐MB‐231 mCherry competitor were mixed 1:1 and injected into the spleen of NOD/SCID/IL2Rγ −/− (NSG) mice (Charles River) as described previously 14 . After 20 to 30 days following the surgery, the mice were perfused with PBS and the liver was harvested.…”
Section: Methodsmentioning
confidence: 99%
“…12 We have previously established the breast cancer PDX mouse model, in which CD44 + cancer cells spontaneously metastasized and formed micrometastases at distant sites. 14,28,29 To characterize the breast CSCs that are involved in metastatic progression, we analyzed the human breast cancer PDX (KUB06) mouse generated by orthotopic xenotransplantation of luminal-type human breast cancer tissues. 28 This PDX mouse is characterized by the formation of micrometastases in the liver when the diameter of tumors at the primary site reached ~2 cm ( Figure 1A).…”
Section: Upregulation Of S100a10 In the Cd44 + Breast Cancer Pdx Cementioning
confidence: 99%
“…Recently, the analysis of metastasized, CD44 + , patient-derived breast cancer cells engrafted into mice revealed that miR-93, as well as miR-25 and miR-106b, were downregulated [ 43 ]. In vitro, miR-93 overexpression significantly hindered breast cancer cell invasion and 3D-organoid growth, and in vivo, it suppressed their ability to metastasize to the liver.…”
Section: Controlling Invasion and Metastasis Through Wasf3 And Micmentioning
confidence: 99%
“…The forced expression of WASF3 in vitro, however, was seen to override miR-93’s ability to suppress breast cancer invasion. Accordingly, metastasized CD44 + cancer stem cells in patient-derived xenograft mice were revealed to significantly upregulate WASF3 mRNA and, as previously mentioned, downregulate miR-93 in comparison to primary cancer stem cells [ 43 ]. Although the exact functional relevance of miR-93’s interaction with WASF3 is not yet clear, miR-93’s possible capacity to impede WASF3 regulation, for example, of stem cell properties, may provide a useful tool in future therapeutic development.…”
Section: Controlling Invasion and Metastasis Through Wasf3 And Micmentioning
confidence: 99%